A Bioinspired Stress‐Response Strategy for High‐Speed Soft Grippers. Issue 21 (2nd September 2021) - Lin, Yangqiao; Zhang, Chao; Tang, Wei; Jiao, Zhongdong; Wang, Jinrong; Wang, Wei; Zhong, Yiding; Zhu, Pingan; Hu, Yu; Yang, Huayong; Zou, Jun
Abstract: The stress‐response strategy is one of the nature's greatest developments, enabling animals and plants to respond quickly to environmental stimuli. One example is the stress‐response strategy of the Venus flytrap, which enables such a delicate plant to perceive and prey on insects at an imperceptible speed by their soft terminal lobes. Here, inspired by this unique stress‐response strategy, a soft gripper that aims at the challenges of high‐speed dynamic grasping tasks is presented. The gripper, called high‐speed soft gripper (HSG), is based on two basic design concepts. One is a snap‐through instability that enables the HSG to sense the mechanical stimuli and actuating instantly. The other one is the spider‐inspired pneumatic‐powered control system that makes the trigger process repeatable and controllable. Utilizing the stress‐response strategy, the HSG can accomplish high‐speed sensing and grasping and handle a dynamic grasping task like catching a thrown baseball. Whereas soft machines typically exhibit slow locomotion speed and low manipulation strength for the intrinsic limitations of soft materials, the exploration of the stress‐response strategy in this study can help pave the way for designing a new generation of practical high‐speed soft robots. Abstract : Inspired by the stress‐response strategy of the Venus flytrap—combining trigger hairs and bistable lobes to accomplish the predation process, the stress‐response strategy with passive sensing and actuating are applied in a soft gripper, thereby enabling the soft gripper to achieve repeatable high‐speed dynamic gripping as well as controllable trigger sensitivity and force output.